CASH MANAGEMENT: GHANAIAN RURAL BANKS PERSPECTIVE - Okyere-Kwakye, Eugene; Amankwaa, Twum; Anane, Emmanuel (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2012)
Rural banking is quiet prevalent in Africa perhaps Ghana. Current research shows that its existence has contributed immensely to the rural community development in the country, hence its description as the financial engine for a countrys growth. Knowing its relevance to the development of a country, and it not being a full fledge bank, there is the need to conduct an empirical study to examine its financial œmodus operandio specifically cash management mechanisms. Therefore the main objective of this paper is to investigate rural banks cash management policies in Ghana using float management techniques, collection techniques, disbursement control and investment of idle cash as its main variables. Questionnaire was used to collect data from one Rural Bank and SPSS was used to analyze the data. The study found that, the collections and disbursements activities of the rural banks do not create any float; that disbursements are always higher than collections; that the difference between collections and disbursements is very significant; that there is no relationship between collections and disbursement. The practical implication of the findings are discussed.